Estudos eletropalatográficos na fala normal e alterada decorrente da fissura labiopalatina - Marisa de Sousa Viana Jesus (2012)
This research aims to make an articulatory description of the consonantal phones of Portuguese language, with a phonetic perspective. More specifically, to analyse the linguopalatal contact in the production of each phone. Having this in mind, three studies were developed, one concerning the articulatory description of consonantalphones in normal speech, a second one on consonantal phones in impaired speech resulting from cleft lip and palate, and a third study, an analysis about linguistic coarticulation in clusters. They were made with two adult male speakers, one with normal speech and another one with impaired speech. The words which compound the corpus contain the phones [+front]: /s/, /z/, /t/, /d/, /n/, /l/, //,/p/ and /m/, and [-front]: / /, / /, //, / /, /k / and /g/; each phone was in the middle of the word, in thebeginning of the syllable, in stressed position, preceded and followed by the vowel [a]. The data were analysed through Electropalatography, which provides information about linguopalatal contact in real-time, through palatograms and contact index methods. The consonantal description of the normal speech pointed that fricatives are characterised by the absence of central longitudinal axis contact; the stops, by complete constriction in some articulatory region. Among laterals, the phone [l]presented minimal lateral longitudinal contact, and the phone [] presented lateral linguopalatal contact. The tap was characterised by a rapid apicoalveolar contact. In relation to the place of articulation, the alveolars presented more constriction in alveolar and postalveolar regions. Among palatals, the phone [] showed palatovelarconstriction, and the phone [], bigger alveopalatal constriction. The contact between velars was minimal so that it was impossible to identify the constriction in the area registered by the artificial palate. The consonantal description of the impaired speech resulting from cleft lip and palate suggested that the speaker presented an articulatory pattern different from the normal speakers, in most consonants and therewere variations in the place of articulation of the same phone. In the release of lingual fricatives, the linguopalatal contact was minimal or absent; the stops presented a tendency to have an almost total linguopalatal contact; the laterals were released with an articulation close to the normal pattern; therefore, it was observed retreat of the tongue in alveolars and more front velars. The phonetic contrast was performed through manner of articulation fricative, stop, lateral, tap, whichremained in the impaired speech deriving from cleft lip and palate. The third study verified the coarticulatory effect in normal speech, in the clusters [sp], [st], [sk] and [s] so that it can be inferred that the phone [s] showed resistance to coarticulation with [p] and [k], and sensibility to coarticulation with [t] and []. By this mean, when there were no concurrent lingual gestures, the /s/ in coda position influenced the proceeding cluster so that a progressive coarticulation occurred whereas when there were concurrence in lingual gestures, the /s/ was sensible to coarticulation observing mutual coarticulation. These effects were limited to a transition point from one phone to another, with exepction to the cluster [s]. Its verified through these three studies that lectropalatography is an efficient resource to provide details regarding speech production.